2003
DOI: 10.1074/jbc.m204821200
|View full text |Cite
|
Sign up to set email alerts
|

A Selective Role for Phosphatidylinositol 3,4,5-Trisphosphate in the Gi-dependent Activation of Platelet Rap1B

Abstract: The small GTP-binding protein Rap1B is activated in human platelets upon stimulation of a G i -dependent signaling pathway. In this work, we found that inhibition of platelet adenylyl cyclase by dideoxyadenosine or SQ22536 did not cause activation of Rap1B and did not restore Rap1B activation in platelets stimulated by cross-linking of Fc␥ receptor IIA (Fc␥RIIA) in the presence of ADP scavengers. Moreover, elevation of the intracellular cAMP concentration did not impair the G idependent activation of Rap1B. Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
82
1
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(95 citation statements)
references
References 33 publications
(49 reference statements)
10
82
1
1
Order By: Relevance
“…One important intracellular pathway which regulates G i -dependent integrin αIIbβ3 activation is constituted by phosphoinositide 3-kinase (PI 3-K) [56, [67][68][69][70]. PI 3-K isoform p110β regulates integrin activation through a classical lipid kinase-dependent mechanism, involving the small GTPase Rap1 and/or the serine-threonine protein kinase B/Akt (PKB/Akt) [71][72][73][74][75][76], whereas p110γ appears to regulate integrin principally through a non-catalytic signalling mechanism [77,78]. Whether other PI3K class I isoforms such as the p110α or PI3K class II or III isoforms, which are highly expressed in blood platelets, play a role in integrin αIIbβ3 activation remains to be determined.…”
Section: Receptormentioning
confidence: 99%
“…One important intracellular pathway which regulates G i -dependent integrin αIIbβ3 activation is constituted by phosphoinositide 3-kinase (PI 3-K) [56, [67][68][69][70]. PI 3-K isoform p110β regulates integrin activation through a classical lipid kinase-dependent mechanism, involving the small GTPase Rap1 and/or the serine-threonine protein kinase B/Akt (PKB/Akt) [71][72][73][74][75][76], whereas p110γ appears to regulate integrin principally through a non-catalytic signalling mechanism [77,78]. Whether other PI3K class I isoforms such as the p110α or PI3K class II or III isoforms, which are highly expressed in blood platelets, play a role in integrin αIIbβ3 activation remains to be determined.…”
Section: Receptormentioning
confidence: 99%
“…Intracellular Ca 2ϩ and protein kinase C have been proposed to mediate agonist-induced Rap1B activation in platelets (10,11). However, more recently it has been reported that platelet Rap1B can also be activated by stimulation of members of the G i family of heterotrimeric G-proteins in the absence of a Ca 2ϩ increase or protein kinase C stimulation (12)(13)(14)(15). For instance, the ␣ 2A -adrenergic receptor, which couples to G␣ z in platelets, mediates epinephrine-induced activation of Rap1B (12,13).…”
mentioning
confidence: 99%
“…Ras-related protein Rap-1b (an abundant small GTPase), which is the predominant Rap 1 isoform and the most abundant Ras family member in platelets, has been reported to activate downstream GPCRs and upstream integrin a IIb b 3 . Predominantly, ADP stimulates Rap 1b activation mainly via a calcium-independent pathway to activate downstream Gai-coupled P2Y12 receptor, and also activates phosphoinositide 3-kinase and its lipid product phosphatidylinositol 3,4,5-triphosphate (Lova et al 2002;Crittenden et al 2004;Chrzanowska-Wodnicka et al 2005). Hence, the expression of Ras-related protein Rap-1b down regulated after treated with RC is corresponded to CalDAG-GEFI (calcium-DAG-GEF/RasGRP protein family) and PI3K signalling pathways.…”
Section: Discussionmentioning
confidence: 99%